CRAFTSMANSHIP OF UZBEKISTAN: DEVELOPMENT AND ITS CURRENT PLACE IN THE INTERNATIONAL ARENA (Scientific journal of the Fergana State University, 2026)
This article analyzes the historical development of Uzbek handicrafts, their current status, and their place in international markets. Uzbek handicrafts have been demonstrated as a symbol of rich culture and artistic creation throughout centuries. In the conducted research, the preservation of traditional methods in handicrafts, integration of digital technologies, and attraction of new generations to these professions were analyzed. The article examined the competitiveness of handmade products in international markets, export opportunities, and support mechanisms provided by the state. As a result of the research, it was revealed: Uzbek handicrafts, possessing distinctive stylistics, high quality, and artistic value, are strengthening their position in international markets.